﻿Evaluation of Grazing Options During Summer for Growing Heifers – Year 2 - J. K. Farney (Kansas Agricultural Experiment Station Research Reports, 2022)
Developing methods to provide high quality forage through most of the year is important for cattle operations. The purpose of this study was to determine forage management options to offset the summer “slump” with fescue. Four grass pasture treatments (10 pastures total; 4 acres each) were used in a completely randomized design and stocked with growing heifers (n = 49; initial wt 473 ± 60 lb). Pasture treatments consisted of novel fescue (FES), crabgrass (CRAB), bermudagrass (BERM), and sorghum-sudan interseeded into novel fescue (SS-FES). Heifers were weighed and grazed pastures from April to September (153 d). Heifers on FES were continuously grazed. All other pastures were rotationally grazed. Sorghum-sudan was interseeded into fescue pastures in May. Average daily gain (ADG) for the entire grazing period was not different between pasture systems. In contrast to the previous year, there were no differences in heifer gain, ADG, or gain per acre for any of the grazing treatments.
Keywords: sorghum-sudan interseeding; heifer development; Bermuda; crabgrass; fescue